2018
DOI: 10.1108/mrr-02-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management transfer challenges within multinational firms

Abstract: Purpose The paper aims to trace the challenges that multinational companies (MNCs) face as they grow out of their national borders into foreign countries and how they attempt to transfer human resource management (HRM) policies and practices across their subsidiaries for a best-fit HRM model. Design/methodology/approach The paper uses the dilemma theory (involving two opposing values which doing one without the other creates a disadvantage but both cannot be done together) as the main analytical tool and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
0
17
0
2
Order By: Relevance
“…The study's findings revealed that several factors influenced the transfer methods used by the EMNCs' headquarters to transfer their HRM practices to their Nigerian subsidiaries. These factors included home country effects, such as the features of the industry sector, the companies' international structure and strategy, and the international experience and mindset of senior management (Oppong, 2018). Another factor was the host country effect, which included socio-cultural elements and institutional factors, such as the legal and economic environments and the education system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study's findings revealed that several factors influenced the transfer methods used by the EMNCs' headquarters to transfer their HRM practices to their Nigerian subsidiaries. These factors included home country effects, such as the features of the industry sector, the companies' international structure and strategy, and the international experience and mindset of senior management (Oppong, 2018). Another factor was the host country effect, which included socio-cultural elements and institutional factors, such as the legal and economic environments and the education system.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, in systems where the inter-firm labour movement is broad and unconstrained by industrial relations, companies might be reluctant to assign substantial resources to train and develop their employees. Therefore, considerable variation in national systems between countries makes HRM practice transfer problematic (Oppong, 2018;Peng, 2016).…”
Section: Why Multinational Companies Transfer Hrm Practicesmentioning
confidence: 99%
See 3 more Smart Citations